The relationship between lactate dehydrogenase and apolipoprotein A1 levels in patients with severe pneumonia: Lactate Dehydrogenase and Apolipoprotein A1 in Severe Pneumonia - Wang, Jiang; Wang, Ronghua; Zhou, Ying; Ma, Yao; Xiong, Chunyan (Journal of Medical Biochemistry, 2023)
Background: To investigate the relationship between lactate dehydrogenase and apolipoprotein A1 levels and the condition and prognosis of patients with severe pneumonia. Methods: We retrospectively collected 204 patients with severe pneumonia who were hospitalized from January 1, 2019 to December 1, 2021 in our hospital (respiratory intensive care unit (RICU)), and divided into survival group (160 patients) and death group (44 patients) according to their hospitalization outcome. The relationship between lactate dehydrogenase and apolipoprotein A1 levels and general information, disease, and treatment needs of patients with severe pneumonia was analyzed, and lactate dehydrogenase, apolipoprotein A1, neutrophil-to-lymphocyte ratio, hematocrit, C-reactive protein, calcitoninogen, D-dimer, Acute Physiology and Chronic Health Status Rating System II, and Pneumonia Severity Index scores were compared between the survival and death groups. The value of these indicators in determining the prognosis of patients was analyzed using subject operating characteristic (ROC) curves. Logistic regression was used to analyze the risk factors for death from severe pneumonia. Results: The differences were statistically significant (P<0.05) when comparing age and pneumonia typing between the two groups. There was no statistically significant difference between the two groups in terms of gender and total length of stay (P >0.05). There was no statistically significant difference in LDH and ApoA1 levels between male patients and female patients (P>0.05). The differences in LDH and ApoA1 levels were statistically significant (P<0.05) when comparing patients with severe pneumonia at different ages. The differences in LDH and ApoA1 levels between SCAP and SHAP patients were not statistically significant (P>0.05). LDH and ApoA1 levels were higher in patients with severe pneumonia with acute exacerbation of slow-onset lung or MODS during hospitalization than in patients with severe pneumonia without acute exacerbation of slow-onset lung or MODS, with statistically significant differences (P<0.05). The differences were statistically significant (P<0.05) when comparing LDH and ApoA1 levels in patients with severe pneumonia with different PSI grades or APACHE II scores. The differences were statistically significant (P<0.05) when comparing LDH and ApoA1 levels in patients with severe pneumonia with different ICU length of stay. There was no statistically significant difference in LDH and ApoA1 levels when comparing patients with severe pneumonia who required tracheal intubation or sedation and analgesia during hospitalization (P>0.05). LDH and ApoA1 levels in patients with severe pneumonia with different duration of mechanical ventilation were compared with statistically significant differences (P<0.05). LDH and ApoA1 levels in the death group were 105.08 (75.22 140.0), which was significantly higher than 86.66 (62.66 106.14) in the survival group, with statistically significant differences (P<0.05). There was no statistically significant difference in the levels of NLR, HCT, CRP, PCT, DD, PSI scores, and APACHE II scores between the two groups (P>0.05). The AUC for LDH predicting death in patients with severe pneumonia was 0.723 (95% CI (0.579 0.868)) with a sensitivity of 70.7% and specificity of 71.8% at a cut-off value of 289 U/mL, and the AUC for ApoA1 predicting death in patients with severe pneumonia was 0.754 (95% CI (0.616 0.891)) with a cut-off value of at 0.92 mg/mL, the sensitivity was 72.2% and specificity was 73.1%, and the AUC for LDH combined with ApoA1 to predict death in patients with severe pneumonia was 0.873 (95% CI (0.779 0.967)), with a higher area under the line than for the assay alone, with a sensitivity of 85.14% and specificity of 82.83%. Multifactorial dichotomous logistic regression analysis revealed that LDH>289 U/mL and ApoA1<0.92 mg/mL would increase the risk of death from severe pneumonia, with statistically significant differences (OR=4.275, 0.548, P<0.05). Conclusion: Elevated LDH levels and reduced ApoA1 levels in patients with severe pneumonia are valuable in assessing patients’ conditions and prognosis, and can provide assistance in the early assessment of patients’ conditions and diagnosis and treatment.